2010
DOI: 10.1093/ndt/gfp762
|View full text |Cite
|
Sign up to set email alerts
|

Study design and subject baseline characteristics in the ADVANCE Study: effects of cinacalcet on vascular calcification in haemodialysis patients

Abstract: Subjects enrolled in ADVANCE have extensive CAC at baseline. The ADVANCE Study should help determine whether cinacalcet attenuates progression of vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…17 Accordingly, DA might be associated with endothelial dysfunction. Also, vascular calcification, which increases with the duration of dialysis, 18 might be responsible for the impairment of vasoconstriction and for arterial stiffness resulting in IDH. Finally, the observation that in the present study the IDWG was significantly correlated with DA may also contribute to explain the association of IDH with DA.…”
Section: Discussionmentioning
confidence: 99%
“…17 Accordingly, DA might be associated with endothelial dysfunction. Also, vascular calcification, which increases with the duration of dialysis, 18 might be responsible for the impairment of vasoconstriction and for arterial stiffness resulting in IDH. Finally, the observation that in the present study the IDWG was significantly correlated with DA may also contribute to explain the association of IDH with DA.…”
Section: Discussionmentioning
confidence: 99%
“…At present, an ongoing randomized, multicenter phase IV study (ADVANCE) evaluates the effect of cinacalcet combined with low dose vitamin D versus flexible vitamin D dosing on the progression of coronary artery calcification in hemodialysis patients. 118 One study investigating the effect of cinacalcet on cardiovascular morbidity and mortality showed a significant reduction in hospitalization and a trend toward reduced mortality among patients treated with cinacalcet versus placebo. 119 inhibits uremia-related vascular calcifications.…”
Section: Calcimimeticsmentioning
confidence: 99%
“…Cinacalcet, a calcimimetic, makes it easier to achieve consistent control of multiple metabolic disordered parameters by acting directly on the calcium-sensing receptors of the parathyroid gland, which is the core of SHPT pathophysiology [23][24][25][26][27][28][29][30][31] . Several interventional [32][33][34][35][36][37][38][39] and observational studies 17,31,[40][41][42] have demonstrated improved control of biomarkers with cinacalcet.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term treatment with cinacalcet (range: 1-3.5 years) maintains reductions in PTH, Ca, P, and Ca  P, with no evidence of decreasing effectiveness over time 38,43,44 . Several phase IV studies have demonstrated cinacalcet efficacy on biochemical markers [23][24][25][26] and volume coronary artery calcification (CAC) scores, which are a surrogate marker of cardiovascular disease 25,26 . Lastly, a retrospective analysis of combined phase 3 and phase 2 studies showed an effect on mortality, cardiovascular events, fractures, and parathyroidectomies 39 .…”
Section: Introductionmentioning
confidence: 99%